Quality enhancements in Government Finance Statistics since the introduction of the euro: Econometric evidence - Henri Maurer; Sascha Keweloh (European Central Bank (ECB), 2017)
This paper reviews the development of the quality of the main fiscal data released through the Excessive Deficit Pr ocedures (EDP) since the euro's introduction. As such, this paper presents the outcome of various econometric tests based on all the vintages of the annual main fiscal data (deficit, change in debt) to assess whether qualitative progress took place over the years. Sound Government Financial Statistics (GFS) data are indeed crucial in the context of the fiscal surveillance carried out in the EU. Therefore, we find it useful to carry out a study responding to former criticisms which pointed out that Member St ates were beautifying their fiscal data and especially their first notified deficit. It was often assumed that Member States could abuse the initial recording of components which bridge the deficit to the change in debt (the so -called defici t-debt adjustments components). To assess this qualitative development properly, the study goes beyond the simple description of the revisions. It proposes innovative ways to identify whether each step of the revision is caused by the upward change in deficit. The study also seeks to better identify the datasets which triggered the qualitative progress observed.
Keywords: H81; M48; 330; Excessive Deficit Procedure (EDP); recording of fiscal data; reliability of fiscal indicators; revisions of fiscal data; stock-flow adjustments; fiscal rules and creative accounting